2000
DOI: 10.1046/j.1365-2672.2000.00958.x
|View full text |Cite
|
Sign up to set email alerts
|

Serovars of Mycobacterium avium complex isolated from AIDS and non-AIDS patients in Spain

Abstract: NA N . 2000. Antigen fingerprinting based on surface glycolipid antigens was applied to the epidemiology of clinical isolates of the Mycobacterium avium complex from 128 acquired immunodeficiency syndrome (AIDS) and 31 non-AIDS patients from several different regions of Spain. The application of thin-layer chromatography, gas chromatography-mass spectrometry and monoclonal antibodies, combined with ELISA, allowed a facile identification, differentiation and classification of the isolates. The cumulative result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…We next determined the specific serovar for each isolate by directly analyzing the GPL that defines the serovar by TLC. The specific serovar assignment for each isolate was performed based on their R f values and previous literature [26]. The results showed that all isolates, except 2, contain nsGPLs and ssGPLs (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We next determined the specific serovar for each isolate by directly analyzing the GPL that defines the serovar by TLC. The specific serovar assignment for each isolate was performed based on their R f values and previous literature [26]. The results showed that all isolates, except 2, contain nsGPLs and ssGPLs (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…2). Based on our previous reports [25], [26] and the limitations that TLC analysis presents [26], a tentative determination of the serovar for each isolate studied was performed. The results indicated that isolate 1 could be a mixture of Ser.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8][9][10] Among more than 31 serotypes of MAC reported so far, 11) MAC with serovar 1, 4, 8 and 9 were frequently isolated in AIDS patients, and the cumulative results demonstrated that the serovar 4 was predominant in clinical isolates of AIDS patients. 1,12) Stimulation of human peripheral blood mononuclear cells (PBMC) and MonoMAC 6 cells, a human macrophage cell line, with GPL serovar 4 induced production of cytokines TNF-a, IL-1b and IL-6 as well as lipid mediators prostaglandin E 2 and thromboxane B 2 . 13,14) When human PBMC were exposed for 24 h to GPL, especially GPL serovar 4, prior to treatment with phytohemagglutinin and phorbol myristate acetate, Th1 cytokine production such as IL-2 and IFN-g was significantly suppressed.…”
Section: -4)mentioning
confidence: 99%